In Vitro Ferrophilic Responses of Photobacterium damselae subsp. piscicida EKL1 and Characterization of the Fe(III)-Piscibactin Complex - Asiye Esra Eren Eroğlu; Kadriye Toklu; Nazlı Sarıkahya; İhsan Yaşa (Microorganisms)
The Gram-negative marine bacterium Photobacterium damselae subsp. piscicida (Pdp) is a pathogen responsible for pseudotuberculosis in various fish species, posing significant threats to aquaculture. Pdp employs strong virulence mechanisms, one of which is the production of the piscibactin siderophore, which plays a key role in iron acquisition from the host. In this study, we evaluated the ferrophilic properties of the Pdp strain EKL1 in relation to growth and biofilm production. In vitro iron limitation significantly suppressed biofilm formation and planktonic growth in EKL1. We then investigated the anti-biofilm activity of deferoxamine (DFO), an iron chelator used to treat transfusion-induced iron overload in thalassemia patients, against EKL1. DFO strongly inhibited EKL1 biofilm production (by 82.1%), suggesting that iron chelation therapy could be an effective strategy to prevent Pdp-induced photobacteriosis outbreaks. Finally, we characterized the iron-bound form of piscibactin through extensive spectroscopic analyses of the siderophore produced by EKL1. Our findings contribute to the development of novel piscibactin-targeted inhibitors, advancing siderophore-based anti-virulence strategies against Pdp.